Workers' safety behaviors in the off-site manufacturing plant. Issue 3 (5th October 2019) - Liu, Qinjun; Ye, Gui; Feng, Yingbin
Abstract : Purpose: Although research on prefabricated construction has gained increasing attention in recent years, limited efforts have been devoted to investigating safety issues in the off-site manufacture, especially workers' behavioral intentions to work safely. Thus, research is needed to identify the motivational factors determining off-site construction workers' safety behaviors. The purpose of this paper is to investigate workers' safety behavior by examining the determinants of behavioral intention in the off-site manufacturing plants in China. Design/methodology/approach: Theory of planned behavior (TPB) was modified and used in this study to explain how the elements in the hypothesized model interact. Data were collected using a questionnaire. Structural equation modeling technique with partial least-squares estimation was used to analyze the data collected. Findings: The findings of this study indicated that workers' tendency to engage in safety behavior is positively related to attitude toward the behavior, subjective norm, perceived behavioral control and behavioral habit, among which attitude toward the behavior and behavioral habit have most significant influences on safety behavior. This finding provides a better explanation on the pathways and the impacts of the crucial factors on the safety behaviors for the off-site manufacture. Originality/value: The possible innovation of this research lies in its attempt to understand the antecedents of workers' safety behavior in the off-site construction environment, which may make original contributions to construction safety research and practice. The findings of this study contribute to the body of knowledge in TPB. Corresponding countermeasures are put forward in order to improve workers' safety behavior in off-site construction.